Envolvimento dos sistemas adenosinérgico e dopaminérgico no efeito antinociceptivo de um derivado do selenoesterol em modelos de nocicepção aguda em camundongos - Sari, Marcel Henrique Marcondes (2014)
Pain is a complex, multifactorial and protective process essential to the preservation of the integrity of the organisms, but when it becomes persistent its presence is devastating, which considerably reduces the well-being and requires immediate interventions. However, even the drug available therapy exerts relative efficacy, there are some limitations about its use. Taking it into account and the potential pharmacological effects already been described to synthetic organoselenium compounds, the aims of this study were to evaluate the antinociceptive effect of a selenosteroid devirated, p-chloro-selenosteroid (PCS), in acute animal models of nociception as well as to propose the mechanisms by which PCS elicits antinociception and if treatment with PCS triggers any toxic effect. The results showed that the administration of PCS (10 mg/kg, intragastrically, i.g.) significantly reduced nociception behaviours in chemical nociception tests, writhing test induced by acetic acid, glutamate test and formalin test, and thermal nociception test, tail-immersion test. Pre-treatment with caffeine (3 mg/kg, intraperitoneally [i.p.], a non-selective antagonist at adenosinergic receptors), SCH58261 (3 mg/kg, i.p., a selective antagonist at A2A adenosinergic receptors), SCH23390 (0.05 mg/kg, i.p., a selective antagonist at D1 dopaminergic receptors) and sulpiride (5 mg/kg, i.p., a selective antagonist at D2 and e D3 dopaminergic receptors) caused a reduction in the antinociceptive action of PCS. By contrast, pretreatment with WAY100635 (0.7 mg/kg, i.p., a selective antagonist at 5-HT1 dopaminergic receptors), ketanserin (0.3 mg/kg, i.p., a selective antagonist at 5-HT2A/2C dopaminergic receptors), ondasentron (0.5 mg/kg, i.p., a selective antagonist at 5-HT3 dopaminergic receptors), L-arginine (600 mg/kg, i.p.) and naloxone (1 mg/kg, subcutaneous [s.c.], a non-selective antagonist at opiod receptors) did not abolish the antinociceptive effect caused by PCS administration. Besides, PCS administration did not caused any alteration neither in plasma aspartate and alanine aminotransferase activities (AST and ALT, respectively), nor in plasma levels of urea, cholesterol and triglycerides, as well as in locomotor and exploratory activities in the animals. In conclusion, the results showed that PCS had antinociceptive action in different models of pain without causing acute toxic effects in mice. The contribution of adenosinergic and dopaminergic systems was demonstrated in PCS action.